1990
DOI: 10.1210/jcem-71-4-806
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Proteins in Maternal Serum Throughout Gestation and in the Puerperium: Effects of a Pregnancy-Associated Serum Protease Activity*

Abstract: The cDNAs encoding three major insulin-like growth factor-binding proteins (IGFBPs) have been cloned and sequenced. We have examined, by Western ligand blotting, the profiles of these binding proteins in human female serum in the normal menstrual cycle, throughout pregnancy, and during the postpartum period. There was no change in the serum profile of any of the binding proteins in early pregnancy compared to that in the secretory phase of the menstrual cycle. However, there was a marked decrease in circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
178
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(194 citation statements)
references
References 58 publications
14
178
2
Order By: Relevance
“…Other studies have shown that the serum concentrations of IGFBP-1, unlike IGFBP-3, increase during pregnancy [25,[32][33][34], and are high in the fetus and newborn [35,36], which was consistent with our results obtained in both normal and diabetic subjects. In addition, we found that they were significantly higher in IDDM mothers and their infants.…”
Section: Relation Between Birth Weight and Serum Concentrations Of Fesupporting
confidence: 93%
See 2 more Smart Citations
“…Other studies have shown that the serum concentrations of IGFBP-1, unlike IGFBP-3, increase during pregnancy [25,[32][33][34], and are high in the fetus and newborn [35,36], which was consistent with our results obtained in both normal and diabetic subjects. In addition, we found that they were significantly higher in IDDM mothers and their infants.…”
Section: Relation Between Birth Weight and Serum Concentrations Of Fesupporting
confidence: 93%
“…4), due to the increased protease activity for IGFBP-3 in pregnant serum [24][25][26]. There was also no difference among the three groups in the amount of 30 KDa species (data not shown).…”
Section: Maternal and Fetal Igfbpmentioning
confidence: 87%
See 1 more Smart Citation
“…A serine protease that specifically degrades IGFBP-5 in fibroblasts has been reported (Nam et al, 1994). In pregnancy, a serum protease exists that degrades IGFBP-3 (Giudice et al, 1990). In all of these conditions, IGFBP degradation, specific or general, resulted in enhanced IGF activity, and dysregulation of this process may promote autonomous growth.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…16,17 In the circulation, IGFBP-3 binds to approximately 95% of IGF-I and IGF-II and this complex prolongs the half-life of IGFs and protects them from degradation. [16][17][18][19] An endogenous pregnancy-related IGFBP-3 proteolytic activity is considered a fundamental mechanism to increase the bioavailability of IGF-I, [20][21][22] which is a mitogenic polypeptide that stimulates cellular proliferation and differentiation and is involved in the regulation of trophoblast invasion and placental development. [23][24][25] In addition, IGFBP-3 can inhibit cell proliferation and stimulate apoptosis via non-IGFdependent pathways.…”
Section: Introductionmentioning
confidence: 99%